Influence of Philosophy on Law and Politics in Western Civilization - Gray L. Dorsey (Washington University Law Quarterly, 1960)
In Western civilization, philosophy has had an influence upon the norms of law and politics and upon attitudes toward legal and political questions and problems. The basic influence, as might be expected, occurred early in the course of Western civilization. It produced a central tradition of natural law and humanism that has had setbacks and various interpretations, but has continued to serve as the guide for law and politics in the Western countries except for the Communists, and for a time, the Germans. However, one of the characteristic attitudes has no present justification, is dangerous, and needs to be changed.
Keywords: Jurisprudence; Philosophy